The Factors Affecting the Unmet Need of Family Planning in Banten Province Year 2019 - Winarni, Lastri Mei; Saputri, Eneng Emi; Nuryanti, Nuryanti Nuryanti; Nugraha, Raden Deden Gumilar (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
The result of Program Accountability Performance Survey (SKAP) year 2019 showed that the data of unmet need of Family Planning comprised 13.9%. It was higher than the result of national SKAP year 2019 which was 12.1% and did not achieve the target of the Strategic Plan 2015-2019 which was 9.91%. The study aimed to investigate the factors affecting the unmet need of Family Planning in Banten Province year 2019. The research method used was quantitative approach with Cross-Sectional research design. The population consisted of all women of childbearing age who did not apply Family Planning listed in SKAP of National Department of Demography and Family Planning (BKKBN) of Banten Province year 2019. The number of samples was 343 respondents. The sampling technique used was total population. The data collection was done using secondary data obtained from the data in SKAP of BKKBN of Banten Province year 2019. The data analysis implemented was univariate, bivariate using chi square, and multivariate using Multiple Logistic Regression Test. The unmet need of Family Planning on the women of childbearing age was 14.0%. Most age of the respondents that was ≥ mean 37.78 years old was found in 182 (53.1%) respondents, married status in 341 (99.1%) respondents, middle family income in 185 (53.9%) respondents, rural residential area in 197 (57.4%) respondents, high-level knowledge ≥ mean 7.10 in 196 (57.1%) respondents. The result of bivariate analysis showed that age had effect on unmet need of Family Planning (p value = 0.000). The variable of marital status, family income, residential area, and knowledge had no effect on unmet need of Family Planning. The dominant factor affecting unmet need of Family Planning was age (p value = 0.000; OR = 6.397).